1991
DOI: 10.1002/cjce.5450690309
|View full text |Cite
|
Sign up to set email alerts
|

Morphological influences in the gas phase polymerization of ethylene by silica supported chromium oxide catalysts

Abstract: Dramatic changes occur during the initial stages of olefin polymerization over heterogenous catalysts. As polymer accumulates, the catalyst fragments and the void space within the growing particle becomes filled with polymer. The changing monomer transport rate to the active sites, dissipation of heat and stress with the particle, and eventually, dispersion of catalyst fragments within the growing particle can control the polymerization. We focus on the changes in, and influence of, polymer, catalyst and void … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 10 publications
1
33
0
3
Order By: Relevance
“…McDaniel 9 and Dalla Lana et al 43 observed very low ethylene polymerization activities over silica-supported Phillips catalysts due to mass-transfer limitations. Webb et al 41 noted that a polymer yield of 0.1 g/g of catalyst rendered the active sites on a silica-supported chromium oxide catalyst inaccessible to ethylene. The fragmentation of the outer layer of the catalyst particles was similar to the initiation of shellwise fragmentation of the catalyst particle from surface to the center as proposed by Bonini et al 44 Once the ethylene transport hindrance by the highcrystallinity polymer in the pores of the catalyst cores occurred, manipulation of the polymerization conditions was ineffective in improving activity.…”
Section: Proposed Catalyst Fracture Mechanism During Ethylene Homopolmentioning
confidence: 99%
See 1 more Smart Citation
“…McDaniel 9 and Dalla Lana et al 43 observed very low ethylene polymerization activities over silica-supported Phillips catalysts due to mass-transfer limitations. Webb et al 41 noted that a polymer yield of 0.1 g/g of catalyst rendered the active sites on a silica-supported chromium oxide catalyst inaccessible to ethylene. The fragmentation of the outer layer of the catalyst particles was similar to the initiation of shellwise fragmentation of the catalyst particle from surface to the center as proposed by Bonini et al 44 Once the ethylene transport hindrance by the highcrystallinity polymer in the pores of the catalyst cores occurred, manipulation of the polymerization conditions was ineffective in improving activity.…”
Section: Proposed Catalyst Fracture Mechanism During Ethylene Homopolmentioning
confidence: 99%
“…40 The polymerization rates of such catalysts are very low for want of monomer at the active sites. 41,42 The artichoke structure of the polymer around the catalyst core was probably produced by polymerization on the external surface of the catalyst particle in combination with small fragments of catalyst breaking off the external Figure 14 Proposed fracture mechanism of low-and high-F polymer-supported metallocene/MAO catalyst particles during gas-phase olefin polymerization. (HDPE, high density polyethylene; LLDPE, linear low density polyethylene).…”
Section: Proposed Catalyst Fracture Mechanism During Ethylene Homopolmentioning
confidence: 99%
“…As discussed by Webb et al, [19] if the catalyst particle can resist the accumulation of mechanical stress, especially at such low reaction rates, the polymer material can clog the catalyst pores and the transport resistance can become the limiting kinetic step. This may eventually lead to depletion of monomer inside the particle and consequently to an overall decrease in the polymerization rate.…”
Section: Case D -The Fluids Have Different Densities and The Catalystmentioning
confidence: 99%
“…The extent of the temperature excursions is of course dependent on a number of parameters (catalyst activity and size and gas velocity). [15][16][17][18][19][20][21][22][23] It is possible to avoid (or eliminate) some of the difficulties occasionally encountered during the early stages of polymerization by choosing conditions such that the initial moments of the reaction occur at rates slower than the potential maximum. This can be done by introducing a prepolymerization step, where the catalyst fragmentation step and initial period of the polymerization occur under milder conditions than in the main reaction, 15 or by designing the catalyst so that the activity profile builds up slowly in the main reactor over the course of several tens of seconds or minutes.…”
Section: Introductionmentioning
confidence: 98%